Hart on Formalism in Legal Reasoning: Implication for Judicial Review - Ngozi Chukwuemeka Aja (Universitas PGRI Madiun, 2022)
This article articulates the implication of Herbert Lionel Adolphus Hart’s views on formalism for judicial review. Formalism in legal reasoning, being adverse to a court’s exercise of discretionary power, defeats the objective of legal reasoning, which is the attainment of justice. The traditional conception of judicial review, which restricts it to the role of the court in establishing the legality of governmental acts, makes legal reasoning formalistic. Hart argues that legal formalism, which means strict adherence to laid-down rules, ought not to be a feature of any aspect of legal reasoning. Thus, legal reasoning in judicial review, if restricted to only establishing the legality of governmental actions and inactions, robs the court of its function in considering both legal and substantive justice. Consequently, this article maintains that the objective of judicial review should also include examining the merit and wisdom of governmental actions and inactions in the light of the principle of substantive justice. Any legal system inclined to realize the principle of substantive justice necessarily deviates from the traditional conception of judicial review. It is sad that even in a country like Nigeria, where recent developments in terms of formulations of fundamental human rights rules and environmental laws point to a change in the traditional conception of judicial review, the Supreme Court still insists on adhering to that conception. The approach adopted by the Nigerian Appeal court in cases of judicial review, which portray a shift from the traditional conception, is commendable and is recommended by this article for every legal system